Unplanned hospitalizations in older patients with cancer: Occurrence and predictive factors. Issue 3 (April 2021) - Lodewijckx, Elke; Kenis, Cindy; Flamaing, Johan; Debruyne, Philip; De Groof, Inge; Focan, Christian; Cornélis, Frank; Verschaeve, Vincent; Bachmann, Christian; Bron, Dominique; Luce, Sylvie; Debugne, Gwenaelle; et al.
Abstract: Background: This study aims to investigate the occurrence of unplanned hospitalizations in older patients with cancer and to determine predictive factors. Methods: A prospective Belgian multicentre ( n  = 22), observational cohort study was performed. Patients ≥70 years with a malignant tumor were included. Patients underwent G8 screening followed by geriatric assessment (GA) if abnormal at baseline and were followed for unplanned hospitalizations at approximately three months. Uni- and multivariable regression models were performed to determine predictive factors associated with unplanned hospitalizations in older patients with an abnormal G8. Results: In total, 7763 patients were included in the current analysis of which 2409 (31%) patients with a normal G8 score and 5354 (69%) with an abnormal G8 score. Patients with an abnormal G8 were hospitalized more frequently than patients with a normal G8 (22.9% versus 12.4%; p  < 0.0001). Reasons for unplanned hospitalizations were most frequently cancer related (25.7%) or cancer therapy related (28%). In multivariable analysis, predictive factors for unplanned hospitalizations in older patients with cancer and an abnormal G8 were female gender, absence of surgery, chemotherapy, ADL dependency, malnutrition and presence of comorbidities. Conclusion: Older patients with cancer and an abnormal G8 screening present a higher risk (23%) for unplanned hospitalizations. Predictive factors for these patients were identified and include not only patient and treatment related factors but also GA related factors.